Penempatan Tenaga Kerja (Pegawai) Dalam Pendidikan Islam (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyse the concept, principles, and implementation of workforce placement in Islamic educational institutions and examine its impact on improving the quality of educational services. The method used is a literature study with a descriptive qualitative approach through an examination of various relevant literature on human resource management based on Islamic values. The results of the study show that employee placement in Islamic education not only considers professional competence but also spiritual, moral, and religious responsibility values. The application of the principle of the right man in the right place supports the creation of a harmonious work environment, increases employee motivation and performance, and strengthens Islamic work culture. Thus, the right placement of personnel contributes directly to the effectiveness of the institution and plays a role in shaping Islamic character and work ethic in the context of education.